2015
DOI: 10.1155/2015/412618
|View full text |Cite
|
Sign up to set email alerts
|

Insufflation with Humidified and Heated Carbon Dioxide in Short-Term Laparoscopy: A Double-Blinded Randomized Controlled Trial

Abstract: Background. We tested the hypothesis that warm-humidified carbon dioxide (CO2) insufflation would reduce postoperative pain and morphine requirement compared to cold-dry CO2 insufflation. Methods. A double-blinded, randomized, controlled trial was conducted to compare warm, humidified CO2 and cold-dry CO2. Patients with benign uterine diseases were randomized to either treatment (n = 48) or control (n = 49) group during laparoscopically assisted vaginal hysterectomy. Primary endpoints of the study were rest pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…The studies all involved laparoscopic operations. Many of the studies had small sample sizes, and only 7 studies had more than 30 patients in each arm [ 22 - 28 ]. Seven studies [ 19 , 23 , 27 , 29 - 32 ] found significantly higher core body temperatures in the treatment group (humidified, warmed CO 2 group) than in the control group (cold, dry CO 2 ) whereas nine studies did not find any significant difference [ 22 , 24 - 26 , 28 , 33 - 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies all involved laparoscopic operations. Many of the studies had small sample sizes, and only 7 studies had more than 30 patients in each arm [ 22 - 28 ]. Seven studies [ 19 , 23 , 27 , 29 - 32 ] found significantly higher core body temperatures in the treatment group (humidified, warmed CO 2 group) than in the control group (cold, dry CO 2 ) whereas nine studies did not find any significant difference [ 22 , 24 - 26 , 28 , 33 - 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 723 papers were identified and entered into a database; 403 were duplicates (same study title appearing in different search results), leaving 320 potentially relevant publications. Thirteen studies met the inclusion criteria and were included in the meta-analysis ( Figure 1) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). They comprised a total of 796 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Another recently published randomised study, which additionally used a warm air blower and warm infusions, did not find any significant temperature difference with the use of HumiGard ® . However, this study cannot be used for comparison as the operation times were very short (average of 15 minutes insufflation time 15 .…”
Section: Discussionmentioning
confidence: 99%